Perceptions of Intra-Familial Child Sexual Abuse and Intimate Parent-Child Interactions - Qian-Wen Xie; Joshua Miller (Asian Social Work Journal, 2018)
The current study aimed to explore Chinese undergraduate students’ perceptions of intimate parent-child interactions (IPCI) and intra-familial Child Sexual Abuse (CSA) as well. 354 undergraduate students from 15 universities or colleges in Beijing were recruited to participate in an online-based survey. Results indicated that IPCI such as co-bathing and co-sleeping were very common among Chinese undergraduate students during childhood. Factors including the child’s age and gender, as well as the parent’s gender involved in IPCI were found to impact respondents’ perceptions of the appropriateness of those interactions. Moreover, respondents’ perceptions of the appropriateness of parent-child intimate interactions might also be influenced by their childhood experiences of parental interactions and their perceptions of intra-familial CSA. The study suggested that distinguishing intra-familial CSA from normative IPCI will continue to be contested and culturally shaped. Comprehensive information and public education about intra-familial CSA are needed for the prevention of CSA in Chinese society.